Effects of wildfire and logging on soil functionality in the short-term in Pinus halepensis M. forests - Lucas-Borja, Manuel E.; Ortega, R.; Miralles, I.; Plaza-Álvarez, P. A.; González-Romero, J.; Peña-Molina, E.; Moya, D.; Zema, D. A.; Wagenbrenner, J. W.; de las Heras, J. (European journal of forest research, 2020)
Salvage logging is thought to have negative impacts on soil functionality because it may increase soil compaction and reduce vegetation cover and soil organic matter content. We investigated whether and to what extent burning and subsequent logging initially altered soil functionality of a Mediterranean forest of Pinus halepensis M. Soil functionality indicators (e.g. soil enzyme activities, basal soil respiration, glomalin-related soil protein, and microbial carbon) were measured in March and October 2017 in unburned forest plots, nearby plots severely burned by wildfire in July 2016, and nearby burned plots severely burned by wildfire and then logged in December 2016 using a lightweight agricultural tractor. The results showed significant differences among three groups: unburned soils sampled in spring (1) and autumn (2), and burned soils (not subject or subject to logging) sampled in spring and autumn. In unburned plots, seasonality had a significant effect, which disappeared in burned plots regardless of whether they had been logged. The burned plots had higher content of organic matter and total nitrogen than the unburned soils but they were not correlated to higher soil respiration or microbial biomass. There were not any differences in any of the soil functionality indicators between the unlogged and logged burned plots. In addition, the burned plots had a higher glomalin-related soil protein content than the unburned soil in the autumn measurement. Overall, the results suggest a short-term wildfire impact of soil properties whereas logging using a lightweight tractor produced no significant impacts in this sparse Mediterranean pine forest.